Mechanisms Underlying Dopaminergic Regulation of Nicotine-Induced Kinetic Tremor - Kato, Masaki; Kunisawa, Naofumi; Shimizu, Saki; Iha, Higor A.; Ohno, Yukihiro (Frontiers in Pharmacology, 2022)
Nicotine induces kinetic tremor, which resembles pharmacological features of essential tremors, via activating the inferior olive (IO) neurons. Since nicotine is known to enhance dopamine release by stimulating α4β2 and/or α6 nACh receptors, we examined the effects of various dopamine receptor ligands on nicotine-induced tremor to clarify the role of the dopaminergic system in modulating nicotine tremor. A tremorgenic dose of nicotine increased the dopamine level in the pons and medulla oblongata (P/MO), and the levels of dopamine metabolites in the hippocampus, P/MO, and striatum. Treatment of animals with the D1/5 agonist SKF-38393 inhibited the induction of nicotine tremor, whereas the D3 agonist PD-128,907 facilitated nicotine-induced tremor. The D2 agonist sumanirole showed no effect. In addition, nicotine tremor was significantly enhanced by the D1/5 antagonist SCH-23390 and inhibited by the D3 antagonist U-99194. Neither the D2 (L-741,626) nor D4 (L-745,870) antagonist affected the generation of nicotine tremor. Furthermore, microinjection of U-99194 into the cerebellum significantly inhibited nicotine-induced tremor, whereas its injection into IO or the striatum did not affect tremor generation. Although intrastriatal injection of SCH-23390 showed no effects, its injection into IO tended to enhance nicotine-induced tremor. The present study suggests that dopamine D3 and D1/5 receptors regulate the induction of nicotine tremor in an opposite way, D3 receptors facilitately and D1/5 receptors inhibitorily. In addition, the cerebellar D3 receptors may play an important role in modulating the induction of nicotine tremor mediated by the olivo-cerebellar system.